REFINE SPLINE RELATED TO THE INTERPOLAR ON AVERAGE ON BASIS OF FIFTH ORDER B-SPLINE - Чолишкіна, О. (Proceedings of National Aviation University, 2012)
The aim is to construct the spline-approximation, taking into account the random kind of the data. In particular, a local refinement of the first degree based on the linear combination of fifth order B-splines, related to the interpolation in the average. In the article is given the explicit form of the proposed spline which applicable to implement the automation of processing sequences of samples observation functions, such as digital signal with finite energy. Formulated and proved the theorem about the value of the spline norm. Comparative analysis of the value norm of the proposed spline-operator with the norms of splines of second to fourth order first degree of refinement shows more stability assessment with substantial oscillation of approximated function